2018
DOI: 10.1016/j.bbadis.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin reductase-A impairment links brain insulin resistance with increased Aβ production in an animal model of aging: Implications for Alzheimer disease

Abstract: Brain insulin resistance is associated with an increased Aβ production in AD although the molecular mechanisms underlying this link are still largely unknown. Biliverdin reductase-A (BVR-A) is a unique Ser/Thr/Tyr kinase regulating insulin signalling. Studies from our group, demonstrated that BVR-A impairment is among the earliest events favoring brain insulin resistance development. Furthermore, reported a negative association between BVR-A protein levels/activation and BACE1 protein levels in the parietal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 97 publications
3
33
0
Order By: Relevance
“…A growing number of studies support a role for impaired autophagy in the development of neurodegenerative diseases, whereby the accumulation of oxidized/unfolded protein contributes to their pathogenesis [33,56]. Previous data from our group collected with regard to AD, DS or aging suggested that mTOR hyper-activation is responsible for the impairment of autophagy resulting in reduced clearance of toxic aggregates, that is, Aβ, hyper-phosphorylated tau and oxidized proteins, which accumulates within the brain [12,23,36,[40][41][42]. Moreover, we noticed that increased oxidative stress levels and protein damage were associated with dysfunctional BVR-A [12,19,23,[26][27][28].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A growing number of studies support a role for impaired autophagy in the development of neurodegenerative diseases, whereby the accumulation of oxidized/unfolded protein contributes to their pathogenesis [33,56]. Previous data from our group collected with regard to AD, DS or aging suggested that mTOR hyper-activation is responsible for the impairment of autophagy resulting in reduced clearance of toxic aggregates, that is, Aβ, hyper-phosphorylated tau and oxidized proteins, which accumulates within the brain [12,23,36,[40][41][42]. Moreover, we noticed that increased oxidative stress levels and protein damage were associated with dysfunctional BVR-A [12,19,23,[26][27][28].…”
Section: Discussionmentioning
confidence: 86%
“…In light of our previous data showing that reduced BVR-A levels or impaired BVR-A activity parallels the hyper-activation of mTOR in both human brain tissue [21,27,36] and in animal models of AD [12,19] or aging [23], the main goal of this study was to evaluate age-associated alterations of mTOR and autophagic flux in the cerebral cortex of a knock-out mouse model for BVR-A (BVR-A −/− ). We provide evidence that loss of BVR-A promotes mTOR hyper-activation, leading to the impairment of autophagy and the subsequent accumulation of oxidatively-damaged proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is clear that BVRA can impact insulin signaling through its interactions with AKT. Others have shown that the loss of BVRA in the brain causes insulin-resistance that occurs in Alzheimer's disease [60][61][62]. However, the loss of BVRA in obesity can result in hyperactivation of insulin signaling [18].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Willette et al found that peripheral insulin resistance is correlated with reduced glucose metabolism in the brain of AD patients, while a positive correlation was observed in the brain of individuals with MCI that then progress to develop AD. Work on animal models of AD, T2D, or insulin resistance also points toward an association between insulin signaling and AD-like pathology (Duarte, 2015;Triani et al, 2018;Sharma et al, 2019). Diverse clinical trials testing the efficacy of insulin to treat AD and MCI are being conducted (Craft et al, 2012;Chapman et al, 2018;Lee et al, 2018).…”
Section: Brain Insulin Resistancementioning
confidence: 99%